Development of Shuttle-Tram Tracking System using IoT and Comparing of Map localization using Google APIs and Custom Map - Thirasit Thothong; Thanavit Anuwongpinit; Piampoom Sarikprueck; Kuson Ta; Thanapat Wilasuwan; Suebsakul Ponthong (My University, 2025)
This paper presents the development of an Internet of Things (IoT)-based Transit Tracking System. At the Faculty of Engineering, King Mongkut's Institute of Technology Ladkrabang, a public transportation system has been developed to facilitate transit around the campus using shuttle cars. Shuttle stations are placed along the routes, and cars run every 10-15 minutes. However, the problem of users not knowing the precise location and arrival time of each shuttle arose. To solve this, a transit tracking system was developed using IoT technology. IoT devices were installed on each vehicle to monitor their real-time locations. The data is collected via GPS and transmitted over the 4G network to a server, then stored in a database and displayed on a website in real-time using React. To reduce costs, a custom map was developed using the Leaflet library as an alternative to the Google Maps API. Testing within the Faculty of Engineering showed that the designed IoT system could transmit data successfully, with a performance of a custom map close to that of the Google Maps API, while also significantly reducing costs.
Keywords: Marine and Coastal Research; Maritime Navigation and Safety; Transportation and Mobility Innovations